Pseudoscalar decays to gauge bosons at the LHC and at a future 100 TeV collider - Arhrib, Abdesslam (2019)
We discuss the search for a CP-odd scalar decaying into gauge bosons in the frameworks of a CP-conserving two-Higgs doublet model (2HDM) and of a 2HDM extended with a vectorlike quark (VLQ) at the Large Hadron Collider and at a future 100 TeV collider. The rate of decay of a pseudoscalar to Z bosons could be important to ascertain the CP nature of the scalars in the model. In the 2HDM A -> ZZ will be extremely hard to detect even at a future 100 TeV pp collider while in the 2HDM+ VLQ this decay can be probed even during the present LHC run. We further discuss all decays of the pseudoscalar into gauge bosons at the LHC and at a future 100 TeV collider in the alignment limit where the lightest scalar is the 125 GeV Higgs with SM-like couplings to the fermions and gauge bosons.